The Effect Of Giving Red Ginger Booked Water On Perineum Wound Healing - Mesrida Simarmata (Institute of Computer Science (IOCS), 2022)
Number Dead Mother (BATTERY) until moment this still high , wrong one the cause is infection . Infection time postpartum can caused because wound perineum which no treated so that no recover . Care wound perineum could conducted by pharmacology and non pharmacology . Wrong one care by non pharmacology is consume ingredient herbs that is drink boiled water ginger red ( Zingiber officinale Var.Rosc.Rubrum ) because contain substance anti- inflammatory . Purpose : for knowing effectiveness drink water stew ginger red ( Zingiber officinaleVar.Rosc.Rubrum ) against healing wound perineum on mother postpartum in Clinic Trismalia Deli Serdang Year 2020. Method : Design study quasi experimenter with design posttest only control group with amount sample 38 respondent , taken by consecutive , data healing perineum obtained by observation . Result : Time healing wound perineum on group respondent drink water white median 16 (min- max : 11-23) whereas group respondent drink boiled water ginger red ( Zingiber officinaleVar.Rosc.Rubrum ) median 13 (min-max :8 -20). After tested with Test Mann- Whitney with score significant 0.002 (p < 0.05) so there is difference time recovery wound perineum mother postpartum on second group that is group drink water stew ginger red ( Zingiber officinaleVar.Rosc.Rubrum ) more fast healed compared to group drink white water . Conclusion : Drink boiled water ginger red ( Zingiber officinaleVar.Rosc.Rubrum ) effective in healing mother's perineal wound breath . Suggestion: Recommended on power health so that give counseling in give water stew ginger red ( Zingiber officinaleVar.Rosc.Rubrum ) for healing perineal wound and on respondent in order to get spread results study for healing wound perineum, for researcher next so that researching to Step which more continued